Quantitative characteristics of rainbow trout (Oncorhynchus mykiss) semen throughout the reproductive season - Şahin, T.; Kurtoglu, I. Z.; Balta, F. (My University, 2014)
The aim of this study was to determine changes in quantitative characteristics of the rainbow trout semen throughout the reproductive season. Semen samples were collected from October to May from broodstock males (n = 12) kept under natural photoperiod regime and semen volume, density, motility, duration of motility, spermatocrit and pH parameters were investigated. In October, one of the 12 brooders (8.3%) were spermiating, increasing to 12 (100%) in December and dropping to 3 (25%) in May. Semen volume significantly increased in January and February. The total volume of expressible semen was maximal in January, increasing from a mean value of 1.7 ml to 20.9 ml. The spermatozoa density showed an increasing trend from October to January, with mean values ranging between 1.4 and 10.3 x 109 sperm/ml. The spermatocrit did not vary with the sampling date. The semen samples collected in November showed the lowest motility of spermatozoa (40%). But the percentage of motile spermatozoa collected from January to May showed more than 80% motility. The duration of motility for the monitoring period ranged between 58.0 and 375.6 sec. In conclusion, the highest quality semen was collected during the medial part of the reproductive season.

Bu çalışmanın amacı üreme mevsimi boyunca gökkuşağı alabalığı spermasının nicel özelliklerindeki değişimleri belirlemektir. Sperma örnekleri doğal fotoperiyot altında tutulan damızlıklardan (n = 12) ekim kasım ayları arasında toplandı. Sperma miktarı ve pH, sperma yoğunluğu ve motilite, motil kalma süresi, spermatokrit belirlendi. Ekimde 12 damızlıktan bir tanesi (%8.3) sperm verirken, aralık ayında sperm veren birey sayısı 12’ye (%100) yükseldi ve mayıs ayında 3 (%3) bireye düştü. Sperma miktarı ocak ve şubat aylarında önemli ölçüde arttı. Sağılabilen sperma miktarı, 1.7 ml’den 20.9 ml’ye yükselerek, ocak ayında en yüksek düzeye çıktı. Ekimde 1.4 x 109 sperm/ml olan spermatozoa yoğunluğu ocak ayında 10.3 x 109 sperm/ml olarak saptandı. Spermatokrit değerleri örnekleme zamanına bağlı olarak değişim göstermedi. En düşük motilite kasımdaki örneklerde, ocak ve mayıs arasında toplanan örneklerde ise %80’den yüskek motilite saptandı. Motil kalma süresi, üreme mevsimi boyunca, 58.0 ve 375.6 s arasında değişti. Sonuç olarak, yüksek kalitede sperma üreme mevsimi ortasında toplandı.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Rainbow trout; Sperm; Spermatological properties; Spawning season; Gökkuşağı alabalığı; Sperma; Spermatolojik özellik; Üreme mevsimi